PENGARUH MODAL USAHA DAN JAM KERJA TERHADAP PENDAPATAN PEDAGANG PASAR PANCASILA DI KOTA TASIKMALAYA - Sundari, Siti; Alin Lindayani (LPPM IAIT, 2023)
The size ofthe working capital used in the business will certainly affectthe income earned by traders. Capitalfor traders is also one of the production factors that affect income levels. The main objective of this studywas to determine the effect of capital and working hours on the income of Pancasila market traders inTasikmalaya City.The method used in this study is a quantitative approach, taking samples using simple random samplingtechnique with a total of 65 respondents. While collecting data with a questionnaire (questionnaire). Dataanalysis used instrument tests consisting of validity and reliability tests, classic assumption tests, hypothesistesting consisting of multiple linear regression tests, t tests, f tests, and R square tests.The results of the study show that: 1) business capital has a positive and significant effect on the income ofPancasila market traders in Tasikmalaya City. 2) working hours do not significantly affect the income ofPancasila market traders in Tasikmalaya City. 3) Simultaneously capital and working hours have asignificant effect on the income of Pancasila market tradersin Tasikmalaya Cit